Needle acquisition patterns, network risk and social capital among rural PWID in Puerto Rico - Ian Duncan; Patrick Habecker; Roberto Abadie; Ric Curtis; Bilal Khan; Kirk Dombrowski (BMC, 2017)
Abstract Background People who inject drugs (PWID) take on significant risks of contracting blood-borne infection, including injecting with a large number of partners and acquiring needles from unsafe sources. When combined, risk of infection can be magnified. Methods Using a sample of PWID in rural Puerto Rico, we model the relationship between a subject's number of injection partners and the likelihood of having used an unsafe source of injection syringes. Data collection with 315 current injectors identified six sources of needles. Results Of the six possible sources, only acquisition from a seller (paid or free), or using syringes found on the street, was significantly related to number of partners. Conclusions These results suggest that sources of syringes do serve to multiply risk of infection caused by multi-partner injection concurrency. They also suggest that prior research on distinct forms of social capital among PWID may need to be rethought.